2018 13th IAPR International Workshop on Document Analysis Systems (DAS) 2018
DOI: 10.1109/das.2018.51
|View full text |Cite
|
Sign up to set email alerts
|

Handwritten Music Object Detection: Open Issues and Baseline Results

Abstract: Optical Music Recognition (OMR) is the challenge of understanding the content of musical scores. Accurate detection of individual music objects is a critical step in processing musical documents, because a failure at this stage corrupts any further processing. So far, all proposed methods were either limited to typeset music scores or were built to detect only a subset of the available classes of music symbols. In this work, we propose an end-to-end trainable object detector for music symbols that is capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…Based on our observations, the main reason of subpar performance of the SSD and R-FCN detectors were the underprediction (by the SSD detector, Figure 7a) and overprediction (by the R-FCN detector, Figure 7b) of egg numbers in the images. Huang, et al [11], Zhang, et al [26], and Pacha, et al [27] also reported that the SSD and R-FCN performed less accurately than faster R-CNN in terms of detecting other types of objects (e.g., handwritten music symbol, wild animal, etc.). Because the SSD detector (with Mobilenet V1 feature extractor) had fewer layers than the other two CNN detectors, it could not obtain as many floor egg features as its counterparts [28].…”
Section: Performance Of the Three Cnn Floor-egg Detectorsmentioning
confidence: 99%
“…Based on our observations, the main reason of subpar performance of the SSD and R-FCN detectors were the underprediction (by the SSD detector, Figure 7a) and overprediction (by the R-FCN detector, Figure 7b) of egg numbers in the images. Huang, et al [11], Zhang, et al [26], and Pacha, et al [27] also reported that the SSD and R-FCN performed less accurately than faster R-CNN in terms of detecting other types of objects (e.g., handwritten music symbol, wild animal, etc.). Because the SSD detector (with Mobilenet V1 feature extractor) had fewer layers than the other two CNN detectors, it could not obtain as many floor egg features as its counterparts [28].…”
Section: Performance Of the Three Cnn Floor-egg Detectorsmentioning
confidence: 99%
“…cropping each staff). A similar approach is [5], where Pacha et al propose an endto-end trainable object detector for music primitives. The proposed method uses a machine-learning approach considering region-based deep convolutional neural networks.…”
Section: Approaches For Handwritten Scoresmentioning
confidence: 99%
“…Although the interest in OMR has reawakened with the appearance of deep learning, as far as we know, the few existing methods that attempt to recognize handwritten scores are mostly focused on solving a particular stage of OMR, such as layout analysis [3] or detection and classification of graphic primitives [4] or music symbols [5,6]. However, in the particular case of Western classical music, music scores are complex documents composed of staves (five horizontal lines), music symbols (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, convolutional-based neural network detectors [6] that merge the segmentation and classification steps have been applied to a variety of dataset like the newly annotated handwritten dataset of modern music, the MUS-CIMA++ dataset [7] or on mensural music scores by [8]. Fully convolutional neural networks have also been used by [9] and [10] which allows for pixel wise segmentation of music symbols.…”
Section: A Optical Music Recognitionmentioning
confidence: 99%